1998
DOI: 10.1097/00005537-199811000-00018
|View full text |Cite
|
Sign up to set email alerts
|

An orthotopic floor‐of‐mouth cancer model allows quantification of tumor invasion

Abstract: We developed an in vivo quantitative cancer invasion model that allows determination of the effect of the expression and activity levels of the proteases MMP-9 and u-PA. Tumor invasion occurred in an orderly and stepwise fashion involving muscles and related vascular, nervous, and bony structures of the floor of the mouth and tongue. This orderly invasion allowed the development of a staging system. We anticipate that this model will have wide applicability in the study of in vivo tumor response to a variety o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
63
0

Year Published

2000
2000
2006
2006

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(65 citation statements)
references
References 19 publications
2
63
0
Order By: Relevance
“…Although each single pathway was previously shown to be involved in MMP-9 production in di erent cellular settings (Huhtala et al, 1991;Moll et al, 1990;Simon et al, 1998Simon et al, , 1999, our study is the ®rst to report that heregulin-b1 can upregulate MMP-9 via simultaneous activation of multiple pathways in breast cancer cells (Figure 6b). The chemical inhibitors we used to block the function of various kinases are reported to be highly speci®c (Simon et al, 1998(Simon et al, , 1999 and caused no apparent phenotypical changes in cells during the assay. Among these, inhibitors that block PKC and p38 pathways had the most potent inhibitory e ects, suggesting that PKC and p38 kinases may be more critical than the Erk kinase in heregulin-b1-mediated MMP-9 induction in breast cancer cells.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…Although each single pathway was previously shown to be involved in MMP-9 production in di erent cellular settings (Huhtala et al, 1991;Moll et al, 1990;Simon et al, 1998Simon et al, , 1999, our study is the ®rst to report that heregulin-b1 can upregulate MMP-9 via simultaneous activation of multiple pathways in breast cancer cells (Figure 6b). The chemical inhibitors we used to block the function of various kinases are reported to be highly speci®c (Simon et al, 1998(Simon et al, , 1999 and caused no apparent phenotypical changes in cells during the assay. Among these, inhibitors that block PKC and p38 pathways had the most potent inhibitory e ects, suggesting that PKC and p38 kinases may be more critical than the Erk kinase in heregulin-b1-mediated MMP-9 induction in breast cancer cells.…”
Section: Discussionmentioning
confidence: 56%
“…In the ®rst model, we hypothesize that there is`cross-talk' between signaling pathways so that blocking one of the signaling pathways may a ect the activation of another pathway. Indeed, some recent publications point out that PKC may function upstream of the p38 kinase pathway (Kozawa et al, 2000;Simon et al, 1998). However, it is unlikely that all three pathways (Erk, p38, PKC) are activated in a sequential order.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, expression of MMP-9 gene is transcriptionally regulated via AP-1, NF-kB and Sp-1 by extracellular factors such as TPA and TNFa (Sato and Seiki, 1993). Participation of the MAPK pathway has been described in the regulation of MMP-9 expression by JNK-and ERK-dependent signaling cascades (Gum et al, 1997) or by p38 MAPK pathway (Simon et al, 1998). We have recently shown that although AP-1 can be regulated via JNK activation, cell-extracellular matrix interactions via ILK can independently regulate AP-1 transcriptional activity through GSK-3b (Troussard et al, 1999).…”
Section: Discussionmentioning
confidence: 97%
“…In another experiment, 10 days after intracerebral injection, pCM vector was injected intraperitoneally twice and the animals killed after 4 months (d) anders, 1996). MMP-9 inhibition in transformed keratinocytes and squamous-cell carcinoma cells was accompanied by reduced invasion through collagen and reconstituted basement membranes (Simon et al, 1998). In addition, there was a reduction in the number of lung colonies formed in an experimental metastasis system in MMP-9 null mice (Itoh et al, 1999) as well as through MMP-9 downregulation (Hua and Muschel, 1996).…”
Section: Discussionmentioning
confidence: 99%